EDD, a novel phosphotransferase domain common to mannose transporter EIIA, dihydroxyacetone kinase, and DegV - Kinch, Lisa N. (Cold Spring Harbor Laboratory Press, 2005)
Using a recently developed program (SCOPmap) designed to automatically assign new protein structures to existing evolutionary-based classification schemes, we identify a evolutionarily conserved domain (EDD) common to three different folds: mannose transporter EIIA domain (EIIA-man), dihydroxyacetone kinase (Dak), and DegV. Several lines of evidence support unification of these three folds into a single superfamily: statistically significant sequence similarity detected by PSI-BLAST; “closed structural grouping” using DALI Z-scores (each protein inside a group finds all other group members with scores higher than those to proteins outside the group) that includes only these proteins sharing a unique α-helical hairpin at the C-terminus and excludes all other proteins with similar topology; similar domain fusions connect Dak and DegV, and genomic neighborhood organizations connect Dak and EIIA-man. Finally, both Dak and EIIA-man perform similar phosphotransfer reactions, suggesting a phosphotransferase activity for the DegV-like family of proteins, whose function other than lipid binding revealed in the crystal structure remains unknown.